2016
DOI: 10.1002/ange.201609515
|View full text |Cite
|
Sign up to set email alerts
|

A Square‐Planar Complex of Platinum(0)

Abstract: Figure 2. Dependence of the potential energy (DE [kcal mol À1 ]) on the N-M-PH 3 angle [8 8]f or 1 sm (Pt) and 2 sm (Pd).Figure 3. Frontier molecular orbitals of 1 sp (left) and 2 dt (right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Nonetheless, considering these computational and experimental findings, a contribution of the sigma bond metathesis pathway is unlikely but possible, and in addition, we cannot rule out other possible outer sphere mechanisms or an FLPlike mechanism involving the labile arm, which was recently reported for a copper pincer complex. 66 In that respect, it is interesting to note that the proposed pathway does not specifically implicate the labile arm, indicating that PN complexes may also be suitable for such transformations. 43,67 Finally, with respect to the resting state and active catalytic species, we also note that during the course of the catalytic reaction, the zinc methyl moiety (denoted X in Figure 4) may be protonated with product (supported by the observation of the proposed complex, PNP tBu *ZnNPhBn, in the equilibrium described above), especially as the concentration of amine or alcohol increases during the reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…Nonetheless, considering these computational and experimental findings, a contribution of the sigma bond metathesis pathway is unlikely but possible, and in addition, we cannot rule out other possible outer sphere mechanisms or an FLPlike mechanism involving the labile arm, which was recently reported for a copper pincer complex. 66 In that respect, it is interesting to note that the proposed pathway does not specifically implicate the labile arm, indicating that PN complexes may also be suitable for such transformations. 43,67 Finally, with respect to the resting state and active catalytic species, we also note that during the course of the catalytic reaction, the zinc methyl moiety (denoted X in Figure 4) may be protonated with product (supported by the observation of the proposed complex, PNP tBu *ZnNPhBn, in the equilibrium described above), especially as the concentration of amine or alcohol increases during the reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…The failure to isolate a pure Cu(I) species by MCR-ALS is assumed to be linked to an intrinsic limitation of the method, known as rank deficiency limitation, which can appear when two distinct chemical species evolve concomitantly, their resulting behavior in the experimental data appears as merged in a single spectral component The higher in-situ reduction temperature and the instability of the occurring Cu(I) intermediate in the Cu(en)2(HCOO)2 complex can be explained as follows: both ethylenediamine ligands only evolve in the last step of the reduction in the Cu(I) → Cu(0) process (see supporting info S13 for TGA-MS). Given the large tetragonal distortion in the Cu(II) complex, a quasi-square planar coordination geometry is imposed on the Cu(I) structure, which is highly disfavored due to its closed d 10 shell electron configuration [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…196 These pincer-type phosphaalkene ligands are of interest due to their stiffening properties. 197,198 Takeuchi and , Choi et al revealed two three-coordinate Cu(I) complexes. The first complex, 185A, was obtained from a reaction of the Eind 2 -BPEP ligand with CuBr(SMe 2 ) in the presence of AgPF 6 .…”
Section: Tungstenmentioning
confidence: 99%
“…A second complex, 185B, with the smaller ligand Mes* 2 -BPEP was obtained analogously (Scheme 63). 198 Hey-Hawkins et al demonstrated the reactivity of bisphosphaalkene diamino compounds toward Mo, W and Cu complexes. The first two were described in the section on Group 6 elements (section 2.3).…”
Section: Tungstenmentioning
confidence: 99%